UTILIZATION OF TREATED WOOD ,STEEL, FIBREGLASS, FERROCEMENT AND ALUMINIUM IN THE CONSTRUCTION OF MORDERN FISHING BOATS AND THEIR COMPARATIVE COST ANALYSIS - RALASUBRAMANYAN, R (Fishery Technology, 2016)
Modern fishing boats have to be built not only on perfect Jines but also with sound and strong construction materials that will ensure a long lasting trouble free service commensurate with the heavy capital investment involved. Choice of construction materials for fishing boats need careful scrutiny as they have to perform too well under most aggressive environments- sea-water and marine atmosphere. A number of alternative boat-building materials are now available whose comparative merits and demerits as well as comparative costs are brought out in this paper.